Haslea silbo and A Novel Cosmopolitan Species of Blue Diatoms - Romain Gastineau (Biology, 2021)
Specimens of a new species of blue diatoms from the genus Haslea Simonsen were discovered in geographically distant sampling sites, first in the Canary Archipelago, then North Carolina, Gulf of Naples, the Croatian South Adriatic Sea, and Turkish coast of the Eastern Mediterranean Sea. An exhaustive characterization of these specimens, using a combined morphological and genomic approach led to the conclusion that they belong to a single new to science cosmopolitan species, Haslea silbo sp. nov. A preliminary characterization of its blue pigment shows similarities to marennine produced by Haslea ostrearia, as evidenced by UV–visible spectrophotometry and Raman spectrometry. Life cycle stages including auxosporulation were also observed, providing data on the cardinal points of this species. For the two most geographically distant populations (North Carolina and East Mediterranean), complete mitochondrial and plastid genomes were sequenced. The mitogenomes of both strains share a rare atp6 pseudogene, but the number, nature, and positions of the group II introns inside its cox1 gene differ between the two populations. There are also two pairs of genes fused in single ORFs. The plastid genomes are characterized by large regions of recombination with plasmid DNA, which are in both cases located between the ycf35 and psbA genes, but whose content differs between the strains. The two sequenced strains hosts three plasmids coding for putative serine recombinase protein whose sequences are compared, and four out of six of these plasmids were highly conserved.